Pengaruh Pembiayaan Mudharabah, Musyarakah dan Murabahah Terhadap Profitabilitas pada PT. Bank Muamalat Indonesia Tbk Periode 2015-2022 - Sahid; Risal Rinofah; Alfiatul Maulida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to test and analyze Mudharabah, Musyarakah, Murabahah financing on the profitability of Bank Muamalat Indonesia. There are several factors analyzed in influencing Profitability, namely Mudharabah, Musyarakah and Murabahah Financing. This study uses a quantitative approach using secondary data, namely data obtained from other parties, books related to the main problem being discussed, websites, documentation, the internet, articles, journals and other written data used as references. based on quarterly reports for the period 2015-2022. Data collection techniques that are not directly shown to the research subjects, but through documents. The documents used can be annual reports and other documents, namely the financial statements of Bank Muamalat and Profit Bank. The data analysis method used in this study is Multiple Linear Regression Analysis. The results of the multiple linear regression test partially show that Mudharabah Financing with a significant value of 0.019, Musyarakah Financing with a significant value of 0.030 and Murabahah Financing with a significant value of 0.008 have a significant effect on Profitability. Simultaneously, all independent variables have a significant effect on Profitability, namely a significant value of 0.000 <0.05.